Sistem Komunikasi Modul Sensor Jamak Berbasiskan Mikrokontroler Menggunakan Serial Rs-485 Mode Multi Processor Communication (Mpc) - wibawa, Suar; Sudana, A. A. K. Oka; Buana, Putu Wira (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 7, No. 2 Agustus 2016, 2016)
Multi-sensor communication system uses RS-485 standard communication connecting each microcontroller-based data processing unit to form BUS topology network. The advantages of this  communication system  are:  connectivity  (easy  to  connecting  devices  on  a  network), scalability (flexibility to expand the network), more resistant to noise, and easier maintenance. The System is built using Master-Slave communication approach model. This system need to filter every data packet on communication channel because every device that connect in this network can hear every data packet across this network. Multi Processor Communication (MPC) model is applied to reduce processor’s burden in inspecting every data packet, so the processor that work in slave side only need to inspect the message for itself without inspecting every data packet across the communication chanel.
Keywords: Multi Processor Communication (MPC); Monitoring system; RS-485